A Soft Organizational Culture and its Impact on Performance Management - the Case of a Unique Consultancy - Kettemer,Lukas; Schramme,Niklas (2017)
We conducted a qualitative study in the consultancy SoftConsulting and took an interpretative and critical perspective to analyze our findings. The main purpose of this thesis is to develop a more nuanced understanding of consultancies in terms of organizational culture and of consultants’ identity and motivation. Further, to find out how organizational culture and performance management systems interrelate. We provide a case study of a big consultancy firm. Our empirical data was collected through interviews with HR personnel and consultants and interpreted with an hermeneutical approach. The culture at SoftConsulting seems to be noticeably different from the traditional view on consultancies, distinctly softer. This becomes apparent in a positive, helpful atmosphere without competition as well as in the self-perception and motivation of consultants. The consultant's identity is rather based on being decent persons than on being a superior elite. The motivation of consultants is based on internal values and social factors rather than on external incentives. The performance management, managerial practices such as feedback and the attitudes of senior management contrast this soft culture and rather fit to the classic tough understanding of consultancies. We name this phenomenon, when organizational systems and practices clash with the organizational culture lived and proclaimed by employees „cultural antagonism“.
Keywords: Organizational Culture; Consultancies; Consultants; Performance Management; Identity; Employee Motivation; Interactive Motivation; Work-life-balance; Modern Working Life; Cultural Antagonism